Understanding the Role of Spiritual Resilience in Maintaining Marital Stability: Preventing Divorce - Fauziah, Meli; Octavia, Vera; Toha, Anis Malik (Analisa: Journal of Social Science and Religion, 2024)
Divorce is a complex challenge in the institution of marriage that affects individuals and society at large. This study examines the idea of spiritual resilience to comprehend the internal elements that contribute to keeping marriages stable. We conducted in-depth interviews and observations with married couples in Cirebon using pertinent case studies. A qualitative analysis was conducted to seek a deeper understanding of the role of spiritual values, beliefs, and practices in strengthening the marriage relationship. This study uses Talcott Parson's theory of structural functionalism to explore how marital resilience affects marital stability and reduces the risk of divorce. Through an analytical approach, this article highlights the contribution of spiritual resilience in preventing divorce and provides insights into how to integrate this concept into marriage counseling intervention programs and practices. As such, this article contributes to a better understanding of the important role of spiritual resilience in strengthening marital relationships and preventing divorce in contemporary society.